DO IT! Marketing : 77 Instant-Action Ideas to Boost Sales, Maximize Profits, and Crush Your Competition - Newman, David, 1964- (AMACOM/American Management Association, 2013)
Kick your business into high gear with this fast, fun, pull-no-punches guide.